1999
DOI: 10.1016/s1074-5521(99)80128-8
|View full text |Cite
|
Sign up to set email alerts
|

Towards subunit-specific proteasome inhibitors: synthesis and evaluation of peptide α', β'-epoxyketones

Abstract: Optimization of amino-terminally acetylated peptide alpha',beta'-epoxyketones furnished a potent proteasome inhibitor, Ac-hFLFL-epoxide, that has an excellent selectivity for the chymotrypsin-like activity. The inhibitor also proved to be a potent antiproliferative and anti-inflammatory agent. The strong in vivo and in vitro activities suggest that this class of proteasome inhibitors could be both molecular probes and therapeutic agents.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
112
0
1

Year Published

2001
2001
2018
2018

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 146 publications
(118 citation statements)
references
References 44 publications
5
112
0
1
Order By: Relevance
“…Numerous studies on proteasomal substrate specificity have been carried out with peptide-based covalent inhibitors. [34][35][36][37][38][39][40] These studies highlight the importance of non-P1 interaction in defining and tuning substrate specificity. X-ray crystallography has proven very useful in the determination of the factors dictating the substrate specificity of the proteasome.…”
Section: Discussionmentioning
confidence: 89%
“…Numerous studies on proteasomal substrate specificity have been carried out with peptide-based covalent inhibitors. [34][35][36][37][38][39][40] These studies highlight the importance of non-P1 interaction in defining and tuning substrate specificity. X-ray crystallography has proven very useful in the determination of the factors dictating the substrate specificity of the proteasome.…”
Section: Discussionmentioning
confidence: 89%
“…It should be noted that, for other class of proteasome inhibitors, at least three amino acid chains are required to moderately inhibit the proteasomal activity. 223,228,235 The most well characterized compound of this class is a dipeptide boronic acid PS-341 (14). 234,236 Analogous to many other proteasome inhibitors that block cell cycle progression, PS-341 treatment also results in accumulation of cells in the G 2 -M phase, 237 eventually leading to apoptosis after prolonged treatments of cells.…”
Section: A Synthetic Proteasome Inhibitorsmentioning
confidence: 99%
“…Examples include TMC-86A (19) and B (20) 255 The facile syntheses of linear peptide α′,β′-epoxyketones has prompted the development of more potent peptide α′,β′-epoxyketones, such as YU101 (23) that was developed by the optimization of the amino acids of the P2-P4 positions to maximize its potency toward the CT-L activity. 235 While lactacystin and epoxomicin are the best known natural product inhibitors of the 20S proteasome, there have been other potent natural product proteasome inhibitors with novel structures. For example, in the course of proteasome inhibitor screening procedure, Kohno et al 257 found a series of TMC-95 (24) from the fermentation broth of Apiospora montagnei Sacc.…”
Section: B Natural Product Proteasome Inhibitorsmentioning
confidence: 99%
“…The nitrophenol group was included at the N terminus because it has been shown to increase the potency of tripeptide vinyl sulfones for the proteasome (19). Libraries were synthesized by coupling a single amino acid in the constant position (C [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19] ) and an isokinetic mixture of this same set of amino acids in a variable position (mix). All natural amino acids were used except cysteine due to its reactivity with the vinyl sulfone.…”
Section: Design and Synthesis Of Positional Scanned Libraries Of Protmentioning
confidence: 99%
“…However, several studies have now established the importance of distal amino acid residues in directing a substrate to an active site in the complex. Detailed kinetic studies using fluorogenic substrates (5) and covalent inhibitors have established the importance of both the P3 and P4 residues for subsite binding (6,7).…”
mentioning
confidence: 99%